Cookie Hijacking: Privacy Risk - Kausar Parveen; Noor Fatima (International Journal for Electronic Crime Investigation, 2023)
Users may accept more cookies than they require because of suspicious behavior in cookie claimers. And, like, more than they even know. So, as we were measuring real behavior, we were also assessing each of these components’ effectiveness, correct? Learning about user opinions of those cookie disclaimers and their entire process of deciding which cookies to accept or, like, reject, bro, was very fascinating. So, guess what? We have conclusively shown that the various images associated with the accept/reject option significantly influence the judgments made by consumers. You won’t believe it, but we also discovered that assigning a label to the rejected option has a really big impact. Further- more, we have confirmed previous studies showing that, well, biased content doesn’t actually have a significant impact on customers’ judgments. To sum up, black patterns in cookie disclaimers are really important. Users are forced to accept more cookies than they really need, and decision-making is greatly influenced by images and labels. Getting folks to accept those cookies is the main goal. According to our research on user attitudes about cookie disclosures, the presence of the disclaimer only slightly affects the way that various user types make decisions. We provide advice on how to improve. Conditions that apply to different user groups.